Sistema psihologicheskoj korrekcii lichnosti sportsmena v olimpijskom sporte - Vysochina, N. (Science in Olympic Sport, 2017)
Knowledge about modern methods of psychological correction of athlete`s personality in Olympic sport has been systematized and generalized on the basis of literary data study. The main directions of influence on athletes` performances are identified. The structure of psychocorrectional techniques is elaborated, which includes psychotherapeutic methods, psychological counselling, and psychological training. The main psychological factors influencing the preparation of athletes are determined. The content and forms of the manifestation of psychological factors during competitive activity are examined and relationship between them is studied. Integral indicators of psychological factors influencing competitive activity in Olympic sport are determined and their priority importance is identified. The results of an expert survey on the influence of psychological factors in Olympic sports (team sports, cyclic sports, complex coordination sports, and combat sports) are analyzed. The system of psychocorrection is developed on the basis of psychological factors influencing the preparation of athletes. The structure of the system includes the complexes of psychocorrection methods, which corresponds to the content-related component of each psychological factor.